The Factors Affecting Customer Loyalty At Conter Ervin Cell Bengkulu Selatan - Akbar Ilahi; Nia Indriasari; Eska Prima Monique (Penerbit Jurnal Indonesia, 2023)
Counter Ervin Cell Bengkulu Selatan is a shop that is engaged in selling Smartphones, selling cards and credits for all operators and serving Hardware, Software and Smartphone Accessories services